X-ray diffraction and SEM/EDX studies on technological evolution of the oxide-fluoride ceramic flux for submerged arc-surfacing - Sokolsky V.E.; Roik A.S.; Davidenko A.V.; Kazimirov V.P.; Lisnyak V.V.; Galinich V.I.; Goncharov I.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The ceramic flux for submerged arc-surfacing with main component composition MgO (10.0 wt. %)-Al2O3 (25.0 wt. %)-SiO2 (40.0 wt. %)-CaF2 (25.0 wt. %) was prepared in a disk dryer-granulator using a sodium/potassium silicate solution as a binder. X-ray powder diffraction (XRPD) collected at r.t. identified α- phase of quartz, Al2O3, MgO and CaF2 of the initial components in the samples taken after granulation and subsequent annealing at 600 °C. In contrast to the low temperature annealing, anorthite (CaAl2Si2O8) is the main phase in the composition of the samples remelted at 1500 °C and quenched subsequently. Chemical analysis performed by means of scanning electron microscopy with energy-dispersive X-ray spectroscopy analysis (SEM/EDX) detects that the grains of the remelted samples possess the same Ca : Al : Si elemental ratio as anorthite. High temperature X-ray diffraction (HTXRD) was used to examine structural transformation in the solid at 600 °C < T < 1200 °C and stages of thermal evolution of ceramic flux were determined. The ceramic flux melts completely at the temperature above 1350 °C. The intensity pattern of the flux melt was obtained by X-ray diffraction of scattered X-rays at 1450 °C. After calculating the structure factor (SF), the radial distribution function (RDF) was evaluated and used to calculate the structural basicity of the flux melt.